The Andromeda strain - Crichton, Michael, 1942-2008. (New York : Avon Books, 2003)
For five days, American scientists struggle to identify and control a deadly new form of life.
Includes bibliographical references (p. [328]-331).
Young Adult
Young Adult
Wilson's Senior High School
840
Keywords: Viruses -- Fiction; Scientists -- Fiction; United States -- Fiction; Viruses -- Fiction; Scientists -- Fiction; United States -- Fiction; Medical novels